The effectiveness of reciprocal study in developing inferential thinking and academic achievement In the subject of the Noble Qur’an and Islamic Education for middle school students - عبد الرحمن اسماعيل وليد (Journal of College of Education, 2021)
The aim of research is to know the effectiveness of the reciprocal teaching strategy in developing inferential thinking and academic achievement in the subject of the Noble Qur’an and Islamic education among middle school students. The researcher adopted theoretical background and previous studies to benefit from them in the research requirements and procedures. Students distributed randomly into two groups, the first is an experimental one,( 29) students studied using the strategy of reciprocal teaching, the second is the control group, and it includes (31) students. He prepared teaching plans for the topics of the Holy Qur’an and Islamic Islamic education in light of the content of the book and the formulated behavioral goals. The researcher formulated (50) behavioral goals and prepared teaching plans for the topics of the Noble Qur’an and Islamic Education in light of the content of the book and the formulated behavioral goals. The researcher prepared an achievement test consisting of (20) paragraphs, as well as a test to measure inferential thinking skills consisting of (20) paragraphs. The mean of the experimental group and the control group in the achievement test, and this is not A difference in favor of the experimental group, as well as the presence of a statistically significant difference .